GIS-BASED LANDFILL SITE SUITABILITY ANALYSIS USING MULTI-CRITERIA WEIGHTED OVERLAY IN SUNGAI PENUH CITY (JOURNAL ONLINE OF PHYSICS, 2026)
Rapid increase in solid waste generation has created significant challenges for environmentally safe landfill planning in many Indonesian cities. Kota Sungai Penuh faces particularly strong constraints due to limited land availability, concentrated settlement patterns, steep terrain, and high hydrological sensitivity. This study evaluates landfill suitability by integrating fifteen environmental and social criteria through the Analytic Hierarchy Process combined with Weighted Overlay Analysis in a geographic information system (GIS) environment. The criteria include terrain conditions, climatic and hydrological variables, land surface characteristics, accessibility, and population related factors. AHP was used to assign weight values and ensure consistency of the pairwise comparison matrix, and all criteria were standardized for weighted spatial integration. The results show four suitability classes, namely Suitable, Moderately suitable, Unsuitable, and Very unsuitable, with no areas categorized as Very suitable. Suitable locations appear only as small and isolated patches on transitional foothill areas, while most of the central basin is unsuitable due to intensive human activity, river proximity, and agricultural land use. Very unsuitable areas dominate the steep mountain slopes surrounding the valley. The findings demonstrate that landfill development in Kota Sungai Penuh is strongly limited by the interaction of terrain, hydrology, climate, and land use factors. The study provides a reproducible spatial framework for supporting informed waste management decisions and can guide planning in other environmentally sensitive regions with similar physical constraints.